De L’excision Au Nord Et À L’ouest De La Côte d’Ivoire - Bakayoko, Ismailia; Gbagbo, Michel K.; Traore, Massandje (European Scientific Journal, ESJ, 2017)
This exploratory study aims at understanding, through the theory of conventions, the social and psychosocial springs underlying the perpetuation of FGM in Côte d’Ivoire. It takes place in the northern and western regions, traditionally favorable to this practice. The approach consisted of interviewing 1008 subjects (women, children, circumcisers, administrative authorities and NGOs) by means of a questionnaire. It concludes with suggestions for strengthening policies in this field.